Fast determination of oxides content in cement raw meal using NIR spectroscopy combined with synergy interval partial least square and different preprocessing methods. (January 2020) - Yang, Zhenfa; Xiao, Hang; Zhang, Lei; Feng, Dejun; Zhang, Faye; Jiang, Mingshun; Sui, Qingmei; Jia, Lei
Graphical abstract: Highlights: NIR spectroscopy was used for compositional analysis of cement raw meal. The proposed method takes only 3–5 min for each measurement. NIR spectra were correlated with oxides content by establishing siPLS models. The established models were optimized by using different preprocessing methods. Abstract: Near infrared (NIR) diffuse reflectance spectroscopy, combined with chemometrics techniques was proposed as a fast and accurate method applied for determination of main components (CaO, SiO2, Al2 O3, Fe2 O3 ) in cement raw meal. The analyses were implemented by correlation of NIR spectra with reference method made by X-ray Fluorescence (XRF), using different regression methods such as partial least square (PLS), interval PLS (iPLS) and synergy interval PLS (siPLS) with multiple pretreatment methods. The optimal models obtained by using siPLS algorithm showed root-mean-square-error-of-prediction (RMSEP) from 0.0379 to 0.1715, the correlation coefficient (Rp ) from 0.7294 to 0.9304 and average prediction error from 0.03% to 0.13%. The proposed method is cheaper and safer, and it takes much less time (3–5 min) than the XRF method (40–60 min) for each measurement. Our results demonstrate that NIR diffuse reflectance spectroscopy technology can be applied to quantitative determination of the four oxides in cement raw meal.